2018
DOI: 10.1038/pr.2018.6
|View full text |Cite
|
Sign up to set email alerts
|

Induction of high-mobility group Box-1 in vitro and in vivo by respiratory syncytial virus

Abstract: Background Despite decades have passed since its discovery, accurate biomarkers of Respiratory syncytial virus (RSV) disease activity and effective therapeutic strategies are still lacking. The high mobility group box type 1 (HMGB1) protein has been proposed as a possible link between RSV and immune system, but only limited information is currently available to support this hypothesis. Methods Expression of HMGB1 gene and protein were analyzed by quantitative PCR, ELISA, Western blot, immunocytochemistry, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…46) Notably, OJPR + macrophages led to overexpression of HMGB1 gene that interacts with nucleosomes, transcription factor, and histones, suggesting that the existence of OJPR within the cell may impart biological potentialityinbothinnateimmunereactionandinflammationmediated pathogenesis as a therapeutic modulator. 47,48) Moreover, marked inhibition of OJPR activity by TLR4 and MAP kinase kinases inhibitor (TAK-242 and PD98059) strongly indicated that OJPR can act as a modulator for TLR4/MyD88 signalcascades.Onthecontrary,OJPRsignificantlyincreased the anti-viral repertoires, including IFNγ, IFNα, OAS1, and Mx1 which are directly associated with anti-viral responses in CD4 + primary T cells. Nonetheless, it remains to be elucidated more about the OJPR under the eukaryote expression system which includes post-transcriptional modification to reachtheirfinalstructurebymolecularchaperones.…”
Section: Discussionmentioning
confidence: 99%
“…46) Notably, OJPR + macrophages led to overexpression of HMGB1 gene that interacts with nucleosomes, transcription factor, and histones, suggesting that the existence of OJPR within the cell may impart biological potentialityinbothinnateimmunereactionandinflammationmediated pathogenesis as a therapeutic modulator. 47,48) Moreover, marked inhibition of OJPR activity by TLR4 and MAP kinase kinases inhibitor (TAK-242 and PD98059) strongly indicated that OJPR can act as a modulator for TLR4/MyD88 signalcascades.Onthecontrary,OJPRsignificantlyincreased the anti-viral repertoires, including IFNγ, IFNα, OAS1, and Mx1 which are directly associated with anti-viral responses in CD4 + primary T cells. Nonetheless, it remains to be elucidated more about the OJPR under the eukaryote expression system which includes post-transcriptional modification to reachtheirfinalstructurebymolecularchaperones.…”
Section: Discussionmentioning
confidence: 99%
“…The biological implications of this mechanism may be of tremendous importance for the pathogenesis of severe pulmonary inflammation because the high constitutive cell surface RAGE expression. It has been demonstrated in preclinical and clinical studies that severe respiratory infections including influenza and human respiratory syncytial virus (HRSV) generate substantial extracellular HMGB1 release in pulmonary inflammation and that HMGB1-specific antagonists ameliorate these conditions (Ito et al 2011;Nosaka et al 2015;Nosaka et al 2018;Hatayama et al 2019;Manti et al 2018;Rayavara et al 2018;Rallabhandi et al 2012;Simpson et al 2020). Extracellular HMGB1 accumulates locally due to passive release from dying cells and active secretion from innate immunity cells and additional cell types.…”
Section: Ragementioning
confidence: 99%
“…Experimental RSV infections respond well to certain therapies that exert multiple biological effects, one of which includes HMGB1 antagonism. Two such examples are glycyrrhizin (Manti et al 2018) and the synthetic TLR4 antagonist eritoran (Rallabhandi et al 2012).…”
Section: Human Respiratory Syncytial Virus (Hrsv)mentioning
confidence: 99%
“…An increase in HMGB1 release has been observed during acute lung injury (ALI) under proinflammatory stimulation [66], but in the same model, autophagy stimulation was effective in reducing HMGB1 release and ALI. In fact, in preclinical and clinical studies, it has been demonstrated that RSV generates extracellular HMGB1 release in pulmonary inflammation and that HMGB1-specific antagonists ameliorate these conditions [67,68].…”
Section: Damage-associated Molecular Patterns (Damps) and Virus Infecmentioning
confidence: 99%